ГОВЬ-АЛТАЙ АЙМАГ, ЧАНДМАНЬ СУМЫН НУТАГТ ОРШИХ АККРЕЦЫН КОМПЛЕКСЫН ГРАНАТАТ АМФИБОЛИТ, АМФИБОЛИТЫН МЕТАМОРФИЗМ - О., Жавхлан; К., Наемура; Д., Энхцацрал; Д., Отгонбаяр; А., Такасу (Geological Issues, 2021)
The eclogite-, ophiolite-, and serpentinite-bearing accretionary complex in the Lake Zone, SW Mongolia occupies the central region of the Central Asian Orogenic Belt. The complex consists mainly of orthogneisses intercalated with eclogites and amphibolite in a mélange zone. Most of eclogites are strongly amphibolitized. In this study, we examined petrography and mineral chemistry of amphibolite and newly found garnet amphibolite within marble. The result of our research shows that metamorphic P-T gradient of Chandman accretionary complex is now can be characterized as low-pressure LT ophiolite zone from the north and medium-pressure MT to HT zones of eclogite-, garnet amphiboliteand serpentinite-bearing units to the south contact with Zamtyn Nuruu basement block. This P-T gradient indicates typical Barrovian-type regional metamorphism.